Controls on the location, morphology and evolution of complex esker systems at decadal timescales, Breiðamerkurjökull, southeast Iceland. Issue 11 (10th March 2015) - Storrar, Robert D.; Evans, David J. A.; Stokes, Chris R.; Ewertowski, Marek
Abstract This paper uses detailed mapping of eskers to address three questions which are important for reconstructing meltwater behaviour beneath contemporary and ancient ice masses: 'What controls the morphology of simple and complex esker systems?', 'How do esker systems evolve through time?' and 'Are esker patterns compatible with groundwater controlled hydraulic spacing of esker tunnels?'. Esker crestlines and widths are mapped on the Breiðamerkurjökull foreland for eight time slices between 1945 and 2007, from high resolution (~50 cm) aerial photography, permitting their long‐term morphological evolution to be analysed in a high level of detail. We find that complex eskers develop where meltwater and sediment is abundant, such that sediment clogs channels, forming distributary eskers. Isolated eskers are simpler and smaller and reflect less abundant meltwater and sediment, which is unable to clog channels. Eskers may take several decades to emerge from outwash deposits containing buried ice and can increase or decrease in size when ice surrounding and underlying them melts out. It has been suggested that groundwater–channel coupling dictates the spacing between eskers at Breiðamerkurjökull. Our results do not dispute this, but suggest that the routing of sediment and meltwater through medial moraines is an additional important control on esker location and spacing. These results may be used to better understand the processes surrounding esker formation in a variety of geographical settings, enabling a more detailed understanding of the operation of meltwater drainage systems in sub‐marginal zones beneath glaciers and ice sheets. Copyright © 2015 John Wiley & Sons, Ltd.